(untitled) (Bangladesh Journal of Urology, 2023)
Background: There are three minimally invasive methods for the treatment of large (>1 cm) upper ureteral stones: ureteroscopic lithotripsy (URSL), percutaneous nephrolithotomy (PCNL) and laparoscopic ureterolithotomy (LUL). With multiple surgical options, the controversy of choosing the best option for a given patient lies. Objective: To compare efficacy and safety between URSL, PCNL and LUL to determine the best choice. Methodology: This study was conducted from March 2020 to February 2022 with 120 patients who had upper ureteral stones admitted at NIKDU. They were randomized into 3 equal URSL, PCNL & LUL groups, 40 patients in each group. The primary outcome was a stone-free rate after 1 month of surgery, and the secondary outcomes were the duration of surgery, length of hospital stay, and complication rate postoperatively. Result: Eight patients needed auxiliary PCNL after URSL and 1 patient after LUL, but none after PCNL. The stone-free rate was 78.1% (25/32) in the URSL group, 95% (38/ 40) in the PCNL group and 100% (39/39) in the LUL group. Operation time was the shortest with URSL and the longest with LUL (all p <0.05). Hospital stay was shorter in the URSL group compared with PCNL & LUL group (p=0.0001). Operation-related complications were almost similar among the three groups. Conclusion: Laparoscopic ureterolithotomy followed by PCNL is the most efficacious modality for treating large upper ureteral stones with a superior stone-free rate and lesser need for auxiliary treatments compared to URSL. Bangladesh J. Urol. 2022; 25(2): 93-97